Ekranisasi Novel Max HavelaarKaryaMultatulli dan Film Max Havelaar Karya Fons Rademakers - Oktaviani, Pramedia; Mu'minin, Mu'minin (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
The phenomenon of dissatisfaction of novel readers and film viewers is no longer a strange thing. This is due to the emergence of studies on ecranisation. This research is a study of ecranisation contained in a novel and film titled Max Havelaar. The focus of the research is divided into three notions, including (1) the process of sampling, (2) the process of adding (3) the process of change varies, more specifically in the characters, plot, and setting. The benefits of this research are for the development of literary studies, more specifically in comparative literary studies. This study uses a qualitative method. There are two research data sources namely (1) Max Havelaar's novel by Multatulli presented by HB Jassin and published by PT Djambat in 2004, and (2) Max Havelaar's film directed by FonsRademakers in 1976. Research data collection techniques. Divided into four steps, including (1) reading, marking and interpreting or making description techniques; (2) Technique of watching and recording every round; (3) techniques for recording data from sources, (4) Data classification techniques using research instruments. The results of this novel and film ekranisasi research found that (1) the shrinking process was dominated by intrinsic figures in additional figures, namely the protagonist named Lucas, Saffelar, Ludwig Stern, Greek Girl, Louise, BesthyRosemeijer, Gaafzuiger, Noni, Saijah's younger siblings . (2) the process of shrinking the channel is dominated by the initial stage, namely the introduction of the figure of BatavusDroggstopel as a coffee broker in the Netherlands.